Karakteristik Cerminan Novel Negeri 5 Menara Karya Ahmad Fuadi Terhadap Karakteristik Siswa Generasi Sekarang - Anjani, Ghifara Firdausa Vidi; Romadona, Tantri Galih; Putri, Ina Hamung; Sudiatmi, Titik (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the characteristics of reflection in the novel Negeri 5 Menara by Ahmad Fuadi in relation to the characteristics of today's generation of students. The novel, which carries the theme of difficulties and ideals, describes the lives of students in Pondok Madani, which are filled with various obstacles in achieving their dreams. This study aims to analyze how the ideals conveyed in this novel reflect the characteristics of today's generation who face technological developments, social problems, and pressure in achieving life goals. The methodology used in this research is qualitative with a descriptive approach. The results of the analysis show that the protagonist, Alif Fikri, represents the characteristics of today's generation, such as resilience, ingenuity, and enthusiasm to face various challenges. The findings of this study reveal that the novel Negeri 5 Menara not only functions as an inspirational narrative, but also has significant relevance in the character building of students. The novel is able to instill the values of independence, critical thinking, and high motivation in realizing dreams, despite facing various limitations that are also experienced by the characters in the story. The characters in this novel come from different backgrounds, but they are able to work together and respect each other's differences, in accordance with the challenges of today's generation living in a multicultural society. In addition, the novel emphasizes the importance of spiritual awareness as the main foundation in building a balanced life, so that it can help students deal with the pressures of life in the modern era that often make them lose their direction and purpose. Values such as the importance of education, friendship, courage in the face of failure, and the spirit of sharing knowledge displayed in this novel are very relevant for the character building of today's students. The novel also has the potential to be an effective learning material in integrating moral values and character education in schools. This research highlights that Negeri 5 Menara can be a source of motivation for students to face contemporary issues with optimism, perseverance, and collaborative spirit. Values such as knowledge, tolerance and courage raised in the story are crucial in shaping students who not only excel academically but also have strong moral character. Thus, Negeri 5 Menara offers great potential as a learning medium capable of effectively integrating character education in the school environment.